A case report on digital preoperative design, clinical application and finite element analysis for a patient with ankylosing spondylitis kyphosis - Zhu, Lei; Zhang, Chi; Peng, Li; Cheng, Zifei; Liang, Xiuwen (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: By assessing a case of ankylosing spondylitis (AS) after thoracic lumbar protrusion deformity in a digital model and verifying its effectiveness after surgery for orthopaedic surgery process simulation, a finite element model was established for biomechanical experiments. Method: A 56-year-old patient with AS underwent preoperative thoracic lumbar spine computed tomography. The data were reconstructed using MIMICS16.0 software and modelled to design and measure the nailing parameters. A three-dimensional model was established using ANSYS14.0 software, and the actual surgical procedure was simulated using biomechanical experiments. The model was verified by comparing the X-ray films obtained from patients during preoperative forward bending, stretching and lateral flexion, with the model further tested using the Hueter-Volkmann principle. Result: On comparing the measurements across three different load cases (forward bending, after stretching and lateral flexion) in patients with AS after thoracic lumbar protrusion deformity and the original X-ray images, no difference was found between the model of deformation and real patient movement displacement across the vertebral body. On simulating the stress distribution, the measured T10-L4 vertebral body stress values at every point in the injured vertebrae were, on the whole, directed at both the upper and lower ends and exhibited a decreasing trend, and the stress distribution gradually decreased from the injured vertebrae (T12 and L1) to the upper and lower ends. Conclusion: The accuracy of the research model is high, the geometric similarity is good and relevant applied anatomy can be undertaken using the model parameter measurement. This study provides a successful example of the application of digital technology in the field of spinal deformity and a novel idea for the treatment of AS-related kyphosis.